P10 Regular low fidelity in-situ simulation picks up latent errors and enhances staff awareness of them. (5th November 2017) - Patel, PH; Burney, N
Abstract : Background: Simulation as an educational tool to raise awareness of human factors in patient safety is well established. Value of simulation education programme is increased by being regular and frequent. By using low fidelity in-situ simulations the demand on finances, venue availability and technical skills of facilitators, that would limit frequency and sustainability of an education programmes, are reduced. In-situ simulation allows staff to 'feel at home' and to explore latent system and environment related errors. Methodology: Two educational fellows ran weekly low to moderate fidelity simulation within our paediatric Emergency department (PED) and general paediatric ward (fortnightly). The simulations were run for 20  min with 1–2 doctors and 2 nursing staffs followed by 30  min debrief sessions. Participant's feedback on the simulation, learning and key action points was sought. We followed up on errors and ensuring action had been taken. Actions may include incorporation of learning in future scenarios. Results: Over 3 months 14 simulation sessions were run. Candidates ranged from FY2, ST1-ST8 paediatric trainees, ST3 EM trainees and band 5–6 nurses. We identified 3 errors that were near misses with the potential for significant harm. 1. A resus trolley that was inappropriately stocked such that it resulted in it being stuck during the scenario. This meant no further equipment including airway tools required at the time were accessible. 2. IM adrenaline dose for anaphylaxis took >15  min to prepare due to unfamiliarity with dose and concentration. An anaphylactic kit with an easy guide is available in the resuscitation trolley but staff members were not aware of this. 3. Resuscitation box for neonates did not include an appropriate stylet that is essential for intubation. This was not available in PED at all or specified on the resuscitation checklist Feedback from candidates highlighted these as learning points and need for further action. Conclusion: Simulations were run with regular frequency with good engagement from staff. We identified latent errors in the system and environment that had potential for moderate to significant harm and empowered staff during debriefing sessions to take preventative actions such as incident reporting, informing seniors and correcting issues. We recommend departmental educational activities incorporate regular in-situ simulation as tool for increasing staff familiarity with their working environment, awareness of potential errors and engagement with clinical governance activity.